Effectiveness of Sanitary Napkins “Love Ms V” on Postpartum Mother’s Comfort and Anxiety Levels - Resta Betaliani Wirata; Erik Adik Putra Bambang Kurniawan (Jurnal Kebidanan dan Kesehatan Tradisional, 2022)
Background: Sanitary napkins’s Love Ms V are sanitary napkins made from special cloth for postpartum mothers used to absorb bleeding in mothers. This study aimed to analyze the effectiveness of using Love Ms V sanitary napkins on the comfort and anxiety levels of postpartum mothers Methods: This research was a quasi experimental study posttest only design with control group. The participants were 70 postpartum mothers that selected by purposive sampling technique and devided into two groups: the intervention group (n=35) received sanitary napkins Love Ms V, and the control group (n=35) received disposible pads. The questionnaire of the comfort and the anxiety was used as a posttest. Mann-Whitney test were employed for data analysis. Results: The increase in comfort level and the decrease in anxiety level was better in the intervention group then that in the control group. There was also a significant difference in the comfort levels (p=0.000) and anxiety levels (p=0.003) postpartum mother between the intervention group and the control group. Conclusion: The sanitary napkins Love Ms V could be considered to use it in hospital practice for postpartum mothers to provide comfort and minimize anxiety, as well as to improve care for postpartum mothers.